Reseña de: Martín Prieto, Pablo, Las Cruzadas. - Cantera Montenegro, Margarita (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2019)
Martín Prieto, Pablo, Las Cruzadas. Madrid, Digital Reasons, 2019, 273 págs. ISBN: 978-84-949317-5-8.